2010
DOI: 10.1261/rna.2188110
|View full text |Cite
|
Sign up to set email alerts
|

The roles of phospholipase C activation and alternative ADAR1 and ADAR2 pre-mRNA splicing in modulating serotonin 2C-receptor editing in vivo

Abstract: The serotonin 2C receptor (5-HT2CR), a Gq-protein-coupled neurotransmitter receptor, exists in multiple isoforms that result from RNA editing of five exonic adenosines that are converted to inosines. In the adult brain, editing of 5-HT2C pre-mRNA exhibits remarkable plasticity in response to environmental and neurochemical stimuli. Here, we investigated two potential mechanisms underlying these plastic changes in adult 5-HT2CR editing phenotypes in vivo: activation of phospholipase C (PLC) and alternative spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…In addition, many alternatively spliced genes that are not regulated by Nova are also RNA editing targets: even the function of both ADAR genes, which are responsible for RNA editing, is regulated through both auto-editing and AS. 30,31 This striking regulatory complexity illuminates the highly reticulate relationships underlying the complex transcriptomes of vertebrate brains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many alternatively spliced genes that are not regulated by Nova are also RNA editing targets: even the function of both ADAR genes, which are responsible for RNA editing, is regulated through both auto-editing and AS. 30,31 This striking regulatory complexity illuminates the highly reticulate relationships underlying the complex transcriptomes of vertebrate brains.…”
Section: Discussionmentioning
confidence: 99%
“…While these two variants have a higher editing efficiency at the A-and C-sites, ADAR1a has higher activity at the B-site [69]. The relative expression of the alternatively spliced ADAR1a and ADAR1b mRNA isoforms correlates with the observed changes at the level of 5HT-2cR RNA editing [70].…”
Section: Adar1 Has Different Promoters and Undergoes Alternative Splimentioning
confidence: 94%
“…In one study, negative feedback on RNA editing was shown to occur through the activation of phospholipase C (PLC) in response to serotonin stimulation [70]. PLC activation leads to the cleavage of phosphatidyl inositol 4,5-bisphosphate to form the second messengers diacylglycerol and inositol 1,4,5-triphosphate, whose successive phosphorylation ultimately leads to the formation of IP6.…”
Section: Inositol Hexakisphosphate In the Catalytic Site Of Adar2mentioning
confidence: 99%
See 2 more Smart Citations